2018
DOI: 10.3390/s18051411
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost, Distributed Environmental Monitors for Factory Worker Health

Abstract: An integrated network of environmental monitors was developed to continuously measure several airborne hazards in a manufacturing facility. The monitors integrated low-cost sensors to measure particulate matter, carbon monoxide, ozone and nitrogen dioxide, noise, temperature and humidity. The monitors were developed and tested in situ for three months in several overlapping deployments, before a full cohort of 40 was deployed in a heavy vehicle manufacturing facility for a year of data collection. The monitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…The microcomputer recorded measurements every 2 s and stored each sensor output locally and also broadcasted the data wirelessly to an on-site server. Validation of other sensors and description of the custom monitor are described in the literature; the gas sensors were evaluated by Afshar-Mohajer, et al [ 24 ], the noise sensor was designed and evaluated by Hallett, et al [ 25 ], and the custom monitors are described by Thomas, et al [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The microcomputer recorded measurements every 2 s and stored each sensor output locally and also broadcasted the data wirelessly to an on-site server. Validation of other sensors and description of the custom monitor are described in the literature; the gas sensors were evaluated by Afshar-Mohajer, et al [ 24 ], the noise sensor was designed and evaluated by Hallett, et al [ 25 ], and the custom monitors are described by Thomas, et al [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Different principles of operation were under discussion to be applied as particle number detectors [4]. The most commonly used PM sensors, such as those in ambient air monitoring [28,29], exposure assessment [30][31][32][33][34], vehicle cabin air quality [35], or even filter monitoring in diesel exhaust [36][37][38], were not applicable to vehicle exhaust due to their relatively large lower size, high detection limit, or slow response time. Currently, there are two concepts for the particle sensors (detectors) inside the on-board systems: condensation particle counters (CPCs), similar to those in laboratory systems, and advanced diffusion chargers (DCs) [4,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…24 We have previously developed a multi-hazard sensor network constructed with low-cost sensors for PM, CO, oxidizing gases (O 3 + NO 2 ) and noise. 33 An industrial hygienist identified hazards at the study site, a heavy-vehicle manufacturing facility, and those of greatest occupational health importance were chosen for inclusion our sensor network. PM has well-characterized associations with cardiopulmonary and respiratory diseases, lung cancer, inflammation, oxidative stress, pulmonary infection, and lung function.…”
Section: Introductionmentioning
confidence: 99%